Draft Annual Plan 1994-95 Andhra Pradesh Volume-II - Planning Commission (Planning Commission, 1994)
This is a major poverty alleviation programme which emphasises the coverage of the poorest of the poor on priority basis. The families below poverty line and more of targeted groups are given preference and are provided with income generating assets and inputs through financial assistance in the form of subsidy equally shared by the State Government and the Central Government and term credit advanced by the Financial institutions. The Government of India releases the funds direct to District Rural Development Agencies towards their share.
Finance and Planning (Plg.Wing) Department Government of Andhra Pradesh
Finance and Planning (Planning Wing) Department Government of Andhra Pradesh